2001
DOI: 10.1002/bit.1100.abs
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pyruvate metabolism in Lactococcus lactis depends on the imbalance between catabolism and anabolism

Abstract: Two strains of Lactococcus lactis ssp. cremoris, MG 1820 and MG 1363, which differed by the presence or absence of the lactose plasmid, respectively, were cultivated in batch-mode fermentation on lactose as carbon substrate. A correlation between the rate of sugar consumption, the growth rate, and the type of metabolism was observed. The MG 1820 strain grew rapidly on lactose and homolactic fermentation occurred. The major regulating factor was the NADH/NAD(+) ratio proportional to the catabolic flux, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…The metabolic pathway shift can be attributed to the control of balancing the redox potential or NADH and NAD + . It has been reported that regulation of pyruvate metabolism in Lactococcus lactis is dependent on the imbalance between catabolism and anabolism (Garrigues et al, 2001;Mercade et al, 2000). A high NADH/NAD + ratio resulted from the imbalance between glycolysis and biomass synthesis can inhibit glyceraldehydes-3-phosphate dehydrogenase (GAPDH) greatly and decrease the glycolysis flux.…”
Section: Effect Of Ph On Metabolic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolic pathway shift can be attributed to the control of balancing the redox potential or NADH and NAD + . It has been reported that regulation of pyruvate metabolism in Lactococcus lactis is dependent on the imbalance between catabolism and anabolism (Garrigues et al, 2001;Mercade et al, 2000). A high NADH/NAD + ratio resulted from the imbalance between glycolysis and biomass synthesis can inhibit glyceraldehydes-3-phosphate dehydrogenase (GAPDH) greatly and decrease the glycolysis flux.…”
Section: Effect Of Ph On Metabolic Pathwaymentioning
confidence: 99%
“…Meanwhile, LDH can be activated strongly by the high coenzyme ratio, and thus, lactic acid production is induced. With the higher xylose metabolism and lower PTB activity at pH 5.3, there probably were initial accumulations of NADH and pyruvate in C. tyrobutyricum cells, and the higher NADH/NAD + ratio activated the LDH (Garrigues et al, 2001) and led to lactate production from pyruvate. On the other hand, the lower xylose metabolic rate and higher PTB activity at pH 6.3 would result in a lower NADH/NAD + ratio, which would not activate LDH.…”
Section: Effect Of Ph On Metabolic Pathwaymentioning
confidence: 99%
“…The regulation of by-products formed by LAB sugar metabolism has been studied extensively, mainly with Lactococcus lactis as the model organism. The work has focused on identification of key metabolites and mechanisms involved in regulating the switch between fermentation modes (7,8,12,13,14,15,18,28,30,39,40).…”
mentioning
confidence: 99%
“…Under anaerobic conditions this constraint results in conversion of glucose into lactate via lactate dehydrogenase (LDH) or into the mixed acid products formate, ethanol, and acetate at a C molar ratio of 1:1:1 via pyruvate formate lyase (PFL) depending on whether the specific sugar uptake rate is high or low (6,12,21). When oxygen is present in the medium, the tight coupling of catabolic carbon fluxes that is needed to satisfy the redox balance is alleviated, since NAD ϩ can be regenerated by the activity of NADH oxidases (NOX).Not only does the presence of oxygen in the medium influence metabolism by altering the NADH/NAD ϩ ratio, which has been proposed to play a key role in regulation of sugar metabolism (12,13,16,17,23), but the cellular content of key enzymes also changes with aeration. The negative effect of oxygen on expression of the pfl gene is well known (1, 22), and PFL is known to be very sensitive to oxygen (10,22,29).…”
mentioning
confidence: 99%